The alleviation of ammonium toxicity in plants - Xiao, Chengbin; Fang, Yuan; Wang, Suomin; He, Kai (Journal of integrative plant biology, 2023)
Nitrogen (N) is an essential macronutrient for plants and profoundly affects crop yields and qualities. Ammonium (NH4+) and nitrate (NO3−) are major inorganic N forms absorbed by plants from the surrounding environments. Intriguingly, NH4+ is usually toxic to plants when it serves as the sole or dominant N source. It is thus important for plants to coordinate the utilization of NH4+ and the alleviation of NH4+ toxicity. To fully decipher the molecular mechanisms underlying how plants minimize NH4+ toxicity may broadly benefit agricultural practice. In the current minireview, we attempt to discuss recent discoveries in the strategies for mitigating NH4+ toxicity in plants, which may provide potential solutions for improving the nitrogen use efficiency (NUE) and stress adaptions in crops. Ammonium is an important inorganic nitrogen source, but it can cause severe toxicity to many plants. This review discusses recent discoveries of strategies for alleviating ammonium toxicity in plants, which may provide potential solutions for improving the nitrogen use efficiency and stress adaptions in crops.